Analisis Pernikahan Usia Dini pada Wanita Usia Subur (Data SKAP BKKBN Provinsi Banten 2019) - Husnul Khotimah; Refi Lindawati (Universitas Faletehan, 2022)
Early marriage is a phenomenon that occurs at the national and international levels, one of which is in Indonesia, according to the results of the Banten Province BKKBN Youth SKAP data in 2019 there are still many people who marry under the age of 18. The purpose of this study was to determine the relationship between education, place of residence, and ethnicity with early marriage in women of childbearing age in Banten Province in 2019. This research was quantitative analytic with a cross-sectional approach. Independent variable; education, place of residence, and ethnicity. The dependent variable is early marriage. Respondents were all data on women of childbearing age contained in the 2019 Banten Province BKKBN SKAP data, which amounted to 1709 people. Data collection uses data from the 2019 Banten Province BKKBN SKAP which is already available. Bivariate data analysis using chi-square. The results showed that there was a significant relationship between education (P: 0.000), place of residence (P: 0.000), and ethnicity (P: 0.000) with early marriage. Education can influence a woman to delay the age of marriage. The longer a woman attends formal education, the higher the age at first marriage, and women who live in rural areas have a higher tendency to marry young than women who live in urban areas and certain ethnic groups have a very close relationship with the occurrence of early marriage.